Accelerometery vs. video-derived stroke parameters in high-level swimmers - Musson, C.; Kramer, M. (South African Journal of Sports Medicine, 2021)
Background: Swimming is a multifaceted sport with nuanced performance parameters that tend to vary according to the swimmer`s stroke style. The extraction and analyses of swim parameters, such as lap time (LT), stroke length (SL), stroke rate (SR) and velocity are time-consuming. This may be eased and to some extent automated by the use of cost-effective tri- axial accelerometers.